2002
DOI: 10.1016/s0376-8716(02)00224-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and age of onset for drug use in seven international sites: results from the international consortium of psychiatric epidemiology

Abstract: This study compares lifetime prevalence and age of first use (onset) for alcohol, cannabis, and other drugs in six international sites. Data from seven epidemiologic field surveys that used compatible instruments and study designs were compiled for cross-site analyses by the International Consortium of Psychiatric Epidemiology (ICPE). The world health organization's composite international diagnostic instrument (WHO-CIDI) and additional items were used to ascertain drug use in each site. Lifetime use rates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
124
3
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(138 citation statements)
references
References 37 publications
5
124
3
6
Order By: Relevance
“…In addition, cocaine was the most "addictive" drug of all the substances used by the community-based comparison population, meaning that among those who have used any substance, the percentage of that group who progress to dependence was the highest. Conditional dependence for cocaine in this population was over 50% which is higher than generally recognized population rates (Vega et al, 2002;Warner et al, 1995). Similarly, in the sibling groups, cocaine was the most addictive for men and women.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…In addition, cocaine was the most "addictive" drug of all the substances used by the community-based comparison population, meaning that among those who have used any substance, the percentage of that group who progress to dependence was the highest. Conditional dependence for cocaine in this population was over 50% which is higher than generally recognized population rates (Vega et al, 2002;Warner et al, 1995). Similarly, in the sibling groups, cocaine was the most addictive for men and women.…”
Section: Discussioncontrasting
confidence: 43%
“…Kendler et al reported a 16%-18% prevalence of lifetime cocaine use whereas 34% of our community based subjects reported cocaine use (Kendler et al, 2003;Kendler and Prescott, 1998). There were also greatly increased rates of dependence in the community sample compared to other population based studies (Vega et al, 2002;Warner et al, 1995). Because our communitybased subjects were matched by zip code, this suggests that socioeconomic or "neighborhood" factors contributed to these elevated rates of drug use and dependence.…”
Section: Discussionmentioning
confidence: 58%
“…Specifically, despite the liberal approach to cannabis use in the Netherlands, rates of cannabis use are substantially lower in that country than in Australia, the US and many other countries. For example, a recent study comparing rates of drug use in seven countries (Vega et al, 2002) noted that the lifetime rate of cannabis use in the Netherlands (12.3%) was less than half of that in the US (28.8%) while a comparable estimate for Australia is that 39.3% of the adult population have used cannabis (Australian Institute of Health and Welfare, 1999). Thus, cannabis use may represent a norm-violating and unconventional behavior in the Netherlands in much the same way as it does in Australia and other countries that adopt more punitive legal approached to cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological studies in different countries have raised concerns regarding an increased risk of psychoactive drug use among adolescents (Vega et al, 2002). This trend towards "normalization" in the use of drugs such as cannabis and cocaine among young people could be especially dangerous for those adolescents with co-morbid psychiatric disorders (Armstrong & Costello, 2002).…”
Section: Introductionmentioning
confidence: 99%